Analysis of Factors Influencing Public Preference for Waqf Products in Islamic Insurance: Evidence in Tasikmalaya City - Rizal, Annas Syams; Yahuza, Bello Sani; Lahuri, Setiawan Bin; Muqorobin, Ahmad (Maliki Islamic Economics Journal, 2024)
This study assesses public interest in waqf insurance within Indonesia's Islamic life insurance sector, utilizing the Analytic Network Process (ANP) to evaluate awareness, trust, and perceptions. Qualitative data from interviews and document analysis supplement the ANP findings, offering a comprehensive understanding of public views. The study emphasizes the importance of innovative marketing strategies in promoting waqf insurance products, revealing that limited public awareness and understanding highlight the need for educational initiatives and targeted marketing. Trust and credibility also play a significant role in consumer decision-making in this niche market. The study suggests that improving public understanding, enhancing accessibility, and fostering trust through regulatory transparency are crucial for increasing participation in waqf insurance. Future study should focus on educational campaigns, transparent communication to build trust, and raise awareness of waqf insurance benefits.